2020
DOI: 10.1016/s2213-8587(20)30061-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of maternal thyroid function with birthweight: a systematic review and individual-participant data meta-analysis

Abstract: Studies on hypothyroidism and hyperthyroidism implicate that adequate maternal thyroid hormone availability is required for optimal fetal growth and development. Studies on the association of mild thyroid function test abnormalities with birth weight report heterogeneous results. Some studies indicate that high FT4 concentrations are associated with lower birth weight which could have implications for the treatment target in women already on levothyroxine therapy. We searched Medline (Ovid), Embase.com, Web-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
104
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(110 citation statements)
references
References 59 publications
4
104
1
1
Order By: Relevance
“…Leon et al [ 56 ] observed that maternal TSH during the first half of pregnancy were inversely related to birth weight and a higher risk of small-for-gestational-age (SGA) newborns. Likewise, a meta-analysis [ 57 ] found significance between maternal subclinical hypothyroidism with a lower mean birth weight than euthyroidism. They also found that isolated hypothyroxinemia was associated with a lower risk of SGA than euthyroidism and a higher mean weight at birth.…”
Section: Discussionmentioning
confidence: 99%
“…Leon et al [ 56 ] observed that maternal TSH during the first half of pregnancy were inversely related to birth weight and a higher risk of small-for-gestational-age (SGA) newborns. Likewise, a meta-analysis [ 57 ] found significance between maternal subclinical hypothyroidism with a lower mean birth weight than euthyroidism. They also found that isolated hypothyroxinemia was associated with a lower risk of SGA than euthyroidism and a higher mean weight at birth.…”
Section: Discussionmentioning
confidence: 99%
“…Both overt and subclinical hypothyroidism poses a risk of placental abruption, preterm delivery, and LBW [21,22] However, the risk for LBW deliveries is lower in mothers suffering from subclinical hypothyroidism as compared to those affected with overt hypothyroidism [23,24]. This has been confirmed by a study by Blazer et al [25] stating that the women affected with hypothyroidism gave birth to LBW infants [25].…”
Section: Discussionmentioning
confidence: 87%
“…Previous effect estimates for the maternal-fetal relationship still warranted replications in large well-designed cohorts. Another recent meta-analysis ( 29 ) aggregated individual-level data of 48,145 mother–child pairs from 20 observational cohorts and detected an inverse association between maternal TSH and FT4 within the normal range and birth weight. Specifically, each 1 SD higher maternal TSH and FT4 was associated with 6 g lower (95%CI, −10 to −2; P = 0.003) and 21 g lower (95%CI, −25 to −17; P < 0.0001) birth weight, respectively.…”
Section: Discussionmentioning
confidence: 99%